Des [videorecording (DVD)] - Arnold, Lewis (Television director); Tennant, David, 1971-; Mays, Daniel; Watkins, Jason, 1966-; Masters, Brian (RLJE Films, 2021)
Follows the investigation into Scottish serial killer Dennis Nilsen after a body is discovered near his home.